Implementation Of Sustainable Prophetic Electoral Rights In The General Election Process - Myaskur, Myaskur (Prophetic Law Review, 2020)
This study aims to examine the function of prophetic electoral rights to strengthen and sustain the cycle of general elections process. It is based on a partial understanding of the right to vote and be elected, which has resulted in corrupt political representatives and officials overriding electoral integrity. Legal issues focus on the nature of prophetic electoral rights and the implementation of prophetic electoral rights that strengthen election integrity in Indonesia. The discussion focuses on the meaning of prophetic electoral rights that have elicited philosophical truth-seeding in the context of humanity, preventing the ugliness in the context of liberation and believing in the power of the great guidance of Allah before, during, and after the election administration cycle. The implementation of prophetic electoral rights begins with all election stakeholders as perfect human beings who are intelligent and conscientious in their endless blessings from Allah in a dignified democratic life. This study suggests promoting the protection of the right to vote in a holistic manner and procedure consistent the values and principles of justice that are explored and understood in wholeness and comprehensiveness of the Qur'an in the rules of election law.Keywords: Prophetic Electoral Rights; Political Corruption; Prophetic EthosImplementasi Hak-Hak Elektoral Profetik Berkelanjutan Dalam Proses Pemilihan HukumAbstrakPenelitian ini bertujuan untuk mengkaji hak-hak elektoral profetik untuk memperkuat dan menopang siklus proses pemilihan umum (pemilu). Hal ini didasarkan pada pemahaman parsial tentang hak untuk memilih dan dipilih, yang mengakibatkan perwakilan dan pejabat politik yang korup mengesampingkan integritas pemilu. Isu hukum fokus pada sifat hak-hak elektoral profetik dan implementasi hak-hak elektoral profetik yang memperkuat integritas pemilu di Indonesia. Pembahasan difokuskan pada pemaknaan hak-hak elektoral profetik yang telah melahirkan penyemaian kebenaran filosofis dalam konteks kemanusiaan, mencegah keburukan dalam konteks pembebasan, dan meyakini keagungan hidayah Allah sebelum, selama, dan setelah proses pemilu. Implementasi hak-hak elektoral profetik dimulai dengan seluruh pemangku kepentingan pemilu sebagai manusia sempurna yang cerdas dan bertakwa atas nikmat Allah yang tiada henti dalam kehidupan demokrasi bermartabat. Kajian ini menyarankan untuk mempromosikan perlindungan hak memilih secara holistis dan prosedur yang konsisten dengan nilai-nilai dan prinsip-prinsip keadilan yang digali dan dipahami secara utuh dan komprehensif dari Al-Qur'an dalam aturan hukum kepemiluan.Kata kunci: Hak-hak Elektoral Profetik, Korupsi Politik, Etos Profetik